Znaczenie i styl tekstu poetyckiego (na przykładzie tomiku "Chwila" i innych wierszy Wisławy Szymborskiej) - Grzeszczuk, Barbara (Stylistyka, 2008)
The article deals with the problem of meaning of a poetic text of economic, lapidary form devoid of linguistic metaphors, where the construction of expression directly reaches the sense. The style of ostensible redundancy is functional in analytical sentences and repetitions, which is connected with the title Chwila. The intention of stopping the time is expressed by the excess of text form, whose function is global meaning. In the analyzed poetry, the meaning is formed by the style; there is not a subject of description in an ontological sense. The elements of the represented world are incompatible and involve a number of choices or options. The meaning lies beyond the scope of reference of text elements. In Szymborska’s poetry, the meaning is not independent. It is not that she chooses appropriate means of expression for already prepared content; for example, when a lofty style is adapted to serious content, or trivial things are spoken playfully about. In Szymborska’s poetry, it is the other way round; a joke, a witticism is the material of her poetry, but the content is serious and concerns the fundamental problems of existence. The lack of loftiness is balanced by omnipresent irony, and the genius of this poetry is underlain by the simplicity and subtlety of medium, the brilliance of expressions and amazing grammar and style as far as linguistics is concerned.